THE DESIGN OF UZBEK NATIONAL MEN'S CLOTHING AND ITS CONNECTION WITH THE MENTALITY - Jo‘rayev Bekzod Omon o‘g‘li (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract:Thearticleexamines the historicalandculturalfoundations of the design of traditionalUzbekmen's clothing.Specialattention is paid to the relationshipbetween the mentality of the Uzbekpeopleand the aestheticelements of the nationalcostume. The article analyzesmoderntrends in men's clothingdesignin the context of preservingnationalidentity.